Real-Time Imaging of a Single Gene Reveals Transcription-Initiated Local Confinement - Germier, Thomas (Biophys J, 2017)
Genome dynamics are intimately linked to the regulation of gene expression, the most fundamental mechanism in biology, yet we still do not know whether the very process of transcription drives spatial organization at specific gene loci. Here, we have optimized the ANCHOR/ParB DNA-labeling system for real-time imaging of a single-copy, estrogen-inducible transgene in human cells. Motion of an ANCHOR3-tagged DNA locus was recorded in the same cell before and during the appearance of nascent MS2-labeled mRNA. We found that transcription initiation by RNA polymerase 2 resulted in confinement of the mRNA-producing gene domain within minutes. Transcription-induced confinement occurred in each single cell independently of initial, highly heterogeneous mobility. Constrained mobility was maintained even when inhibiting polymerase elongation. Chromatin motion at constant step size within a largely confined area hence leads to increased collisions that are compatible with the formation of gene-specific chromatin domains, and reflect the assembly of functional protein hubs and DNA processing during the rate-limiting steps of transcription.